Association between Impulsivity and Critical Health Literacy among College Students - HIGUCHI, Yumi; UEMURA, Kazuki; OTA, Akane; WAKAMATSU, Norika (Journal of Physical Therapy for Prevention, 2025)
Objective: This study aimed to examine the association between impulsivity and critical health literacy among college students.Methods: We conducted a web-based survey in college students. The outcome was critical health literacy obtained from a test for measuring the ability to interpret medical information (TAIMI). Exposure was impulsivity measured using a validated questionnaire. Participants were categorized into tertiles; cautious (T1), average (T2), and impulsive (T3), based on their impulsivity scores. The logistic regression model estimated the odds ratios (ORs) and 95% confidence intervals (CIs) for low TAIMI scores (< 6) and incorrect answers to each question, comparing T2 and T3 with T1 (reference), with adjustment for confounders, including age, sex, faculty, alcohol intake status, exercise habit, sleep duration, and self-reported health status.Results: Overall, 415 individuals (mean age = 20.1 years [standard deviation = 2.1]; 188 [45.3%] men) responded to the survey. Multivariable logistic regression model revealed no significant association between impulsivity scores and critical health literacy. Secondary analyses showed that the impulsive group was more likely to select incorrect options in Q6 of the TAIMI (graph reading) than the cautious group (T2; OR [95%CI] = 1.57 [0.58–4.28], T3; 3.01 [1.21–7.53], P for trend = 0.017).Conclusion: Impulsivity was not associated with critical health literacy in college students. Further research is needed to examine the relationship between impulsivity and graph literacy.